DIGITAL E-DASHBOARD UNTUK RUANG STERILISASI: MENINGKATKAN SISTEM PEMANTAUAN DAN PENGENDALIAN KESEHATAN - Abdul Haris Kuspranoto; Zulkhairi; Muhammad Fa’iz Alfatih (MEDIKA TRADA, 2024)
Effective sterilization is crucial in healthcare settings to prevent healthcare-associated infections (HAIs) and ensure patient safety. Traditional methods of monitoring sterilization environments often involve manual checks and lack real-time data, leading to potential inefficiencies and risks. This paper presents the development and implementation of a Digital E Dashboard designed to enhance the monitoring and control of sterilization rooms. The system integrates an ESP32 microcontroller with various sensors to continuously monitor critical parameters such as temperature, humidity, and UV light intensity. The ESP32 microcontroller serves as the core component, collecting real-time sensor data and transmitting it to a cloud server for storage and further analysis. A web-based user interface provides an intuitive dashboard for healthcare staff, offering real-time visualization of sterilization conditions, historical data analysis, and customizable alert settings. Over an eight-week testing period, the system demonstrated high reliability and accuracy, maintaining optimal sterilization conditions and providing timely alerts for any deviations. Implementing the Digital E Dashboard resulted in significant improvements in workflow efficiency and sterilization process reliability. The system's ability to provide real-time data and automated alerts reduced the need for manual monitoring and allowed for prompt corrective actions, minimizing the risk of HAIs. The results, summarized in a detailed table, showed that the average temperature was consistently maintained within the optimal range of 60-80°C, humidity levels were kept between 30-50%, and UV light intensity was monitored effectively with minimal deviations. Feedback from healthcare staff indicated that the dashboard was user-friendly and significantly enhanced their ability to monitor and control the sterilization environment effectively. While the system proved successful, challenges such as sensor calibration, network connectivity, and user training were encountered. Future developments will focus on integrating additional sensors, enhancing network resilience, and incorporating advanced data analytics for predictive insights. The Digital E Dashboard represents a significant step forward in leveraging modern technology to improve sterilization practices in healthcare settings, ultimately contributing to better patient outcomes and safety.